2019
DOI: 10.1016/j.jclinepi.2019.02.016
|View full text |Cite
|
Sign up to set email alerts
|

The proportion of missing data should not be used to guide decisions on multiple imputation

Abstract: Objectives Researchers are concerned whether multiple imputation (MI) or complete case analysis should be used when a large proportion of data are missing. We aimed to provide guidance for drawing conclusions from data with a large proportion of missingness. Study Design and Setting Via simulations, we investigated how the proportion of missing data, the fraction of missing information (FMI), and availability of auxiliary variables affected MI performance. Outcome data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
504
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 723 publications
(515 citation statements)
references
References 36 publications
9
504
1
1
Order By: Relevance
“…Variables included in our imputation model were those in our analyses (exposures, covariates, outcomes) or predictors of missingness. Predictors of missingness are auxiliary variables selected to inform the generation of unbiased estimates of missing values and to improve the missing at random assumption [43]. We included twelve auxiliary variables from the mothers' and partners' social history during pregnancy and nine auxiliary childhood adversity exposures not part of the WHO ACE International Questionnaire.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Variables included in our imputation model were those in our analyses (exposures, covariates, outcomes) or predictors of missingness. Predictors of missingness are auxiliary variables selected to inform the generation of unbiased estimates of missing values and to improve the missing at random assumption [43]. We included twelve auxiliary variables from the mothers' and partners' social history during pregnancy and nine auxiliary childhood adversity exposures not part of the WHO ACE International Questionnaire.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Researchers in a variety of fields often concern what is the proper scope of application for MI in terms of the proportion of missing data [23]. In this paper we found 30% is the scope of MI.…”
Section: Discussionmentioning
confidence: 64%
“…The analysis models would be the same as other statistical model with complete data sets. Many studies indicated that the imputation model should contain all variables in the analysis model or any auxiliary variables relating with outcome variables likely to be used in the subsequent analyses [19,23]. For each of 30 simulation data sets and the data set K, taking Y 1 as the dependent variable and the others as the covariates for regression analysis.…”
Section: Analysis Modelsmentioning
confidence: 99%
“…Recent research has also shown that the proportion of missing data should not be the major driver for the decision on how to handle missing data. 22 In fact, even when the extent of missing data is large, results can still be unbiased provided that the MAR assumption is met and methods to handle missing data have been adequately applied.…”
Section: Methods To Handle Missing Datamentioning
confidence: 99%